2021
DOI: 10.1039/d1ma00942g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in ultra-low temperature (sub-zero to 100 °C) synthesis, mechanism and applications of titania (TiO2) nanoparticles

Abstract: The development of titania (TiO2) nanomaterials for next-generation photonic, optoelectronic, and catalytic applications necessitates a facile and cost-effective synthetic methodology for precisely tuning the composition, phase, and morphology at nanometer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 190 publications
(320 reference statements)
0
5
0
Order By: Relevance
“…Additionally, the peaks at 140 cm -1 , 391 cm -1 , 513 cm -1 , and 639 cm -1 can be clearly identified, corresponding to the Raman modes of Eg, B1g, A1g, and Eg, respectively, characteristic of TiO2 [4,15,17]. Finally, in the spectra of TiO2@rGO-ST and TiO2@rGO-SG, the same bands attributed to the TiO2 and rGO nanomaterials are found, indicating their presence in the nanocomposites.…”
Section: Raman Spectroscopy Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Additionally, the peaks at 140 cm -1 , 391 cm -1 , 513 cm -1 , and 639 cm -1 can be clearly identified, corresponding to the Raman modes of Eg, B1g, A1g, and Eg, respectively, characteristic of TiO2 [4,15,17]. Finally, in the spectra of TiO2@rGO-ST and TiO2@rGO-SG, the same bands attributed to the TiO2 and rGO nanomaterials are found, indicating their presence in the nanocomposites.…”
Section: Raman Spectroscopy Resultsmentioning
confidence: 74%
“…Diverse semiconductors such as titanium dioxide (TiO2) have been used over time as photoanodes in photoelectrocatalysis (PEC); however, despite its remarkable chemical stability, the wide band gap of TiO2 represents a disadvantage in the process due to the significant recombination of charge carriers and the reduced absorption region, which is only the ultraviolet light region [3,4]. Some studies have shown that the combination of reduced graphene oxide (rGO) with TiO2 improves the photoelectrochemical performance by taking advantage of the adsorption and conductivity capabilities of rGO, thus implying a reduction in the band gap [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The separation of the intermediary [Ti(TIP) 3 (BTO)(OH) 2 ] 2 O (mp-TiBTO) in the preparation TiO 2 –BTO via method A teaches us about the stoichiometry and the sequence of the metathesis and hydrolysis reactions involved in the syntheses and the concurrence between both processes. Traces of water favorable for promoting the metathesis [ 56 ] were enough to simultaneously induce partial hydrolysis, leading to the molecular dimer mp-TiBTO ( Figure 1 b) instead of the monomer. As observed in Table S1 , the same effect is observed for the nanocomposites TiBTO and TiPA-A.…”
Section: Discussionmentioning
confidence: 99%
“…The design and synthesis of TiO 2 with different polymorphs, morphologies, and exposed facets are key to effectively improving their practical application in the field of photocatalysis, as its photocatalytic activities depend critically on the crystal phase, morphology, size, surface area, heterojunction structure, and exposed facets of TiO 2 [5][6][7][8]. Among the four polymorphs of TiO 2 (i.e., anatase, rutile, brookite, and TiO 2 (B)) that mainly exist in nature [9][10][11], anatase usually exhibits the highest photocatalytic activity due to the most increased electron mobility and the lowest photogenerated electron-hole recombination in anatase and the rapid interaction between many organic molecules and anatase surfaces [2]. However, compared with the anatase phase (3.20 eV), brookite phase (3.40 eV), and TiO 2 (B) (3.10 eV), the decreased band gap energy of rutile (3.02 eV) leads to part of the photoresponse extending slightly into the visible light region, thus improving the utilization of sunlight [12].…”
Section: Introductionmentioning
confidence: 99%